A Microphysiological System for Studying Nonalcoholic Steatohepatitis. Issue 1 (13th November 2019) - Kostrzewski, Tomasz; Maraver, Paloma; Ouro‐Gnao, Larissa; Levi, Ana; Snow, Sophie; Miedzik, Alina; Rombouts, Krista; Hughes, David
Abstract : Nonalcoholic steatohepatitis (NASH) is the most severe form of nonalcoholic fatty liver disease (NAFLD), which to date has no approved drug treatments. There is an urgent need for better understanding of the genetic and molecular pathways that underlie NAFLD/NASH, and currently available preclinical models, be they in vivo or in vitro, do not fully represent key aspects of the human disease state. We have developed a human in vitro co‐culture NASH model using primary human hepatocytes, Kupffer cells and hepatic stellate cells, which are cultured together as microtissues in a perfused three‐dimensional microphysiological system (MPS). The microtissues were cultured in medium containing free fatty acids for at least 2 weeks, to induce a NASH‐like phenotype. The co‐culture microtissues within the MPS display a NASH‐like phenotype, showing key features of the disease including hepatic fat accumulation, the production of an inflammatory milieu, and the expression of profibrotic markers. Addition of lipopolysaccharide resulted in a more pro‐inflammatory milieu. In the model, obeticholic acid ameliorated the NASH phenotype. Microtissues were formed from both wild‐type and patatin‐like phospholipase domain containing 3 (PNPLA3) I148M mutant hepatic stellate cells. Stellate cells carrying the mutation enhanced the overall disease state of the model and in particular produced a more pro‐inflammatory milieu. Conclusion: The MPS model displays a phenotype akin to advanced NAFLD or NASH and has utility as a tool for exploring mechanisms underlying the disease. Furthermore, we demonstrate that in co‐culture the PNPLA3 I148M mutation alone can cause hepatic stellate cells to enhance the overall NASH disease phenotype. Abstract : We have developed an advanced human in vitro co‐culture model of nonalcoholic steatohepatitis. The model was used to explore effects of genetic mutations in the PNPLA3 gene on hepatic stellate cell function and disease progression.